Adaptation and validation of the Van Rie tuberculosis stigma scale in Vietnam. (January 2022) - Redwood, Lisa; Mitchell, Ellen M.H.; Nguyen, Thu Anh; Viney, Kerri; Duong, Linh; Phạm, Huu Thuong; Nguyen, Binh Hoa; Nguyen, Viet Nhung; Fox, Greg J.
Highlights: The Van Rie tuberculosis stigma scale (VTSS) is valid and useful for measuring stigma in people with tuberculosis (TB) in Vietnam. The TB/HIV co-infection items could be removed depending on the purpose of the scale. The correlation between the scale and related constructs should be improved. With the increase of valid scales, TB stigma should be measured routinely. Abstract: Objectives: Tuberculosis (TB) stigma contributes to diagnostic delay, disease concealment, and reduced wellbeing for affected individuals. Despite the availability of several TB stigma scales, most high-TB burden countries do not have a culturally validated version available. This study evaluated the Van Rie TB stigma scale (VTSS) among people with TB in Vietnam. Methods: This study consisted of two phases. In phase 1, the VTSS was culturally and linguistically adapted to the Vietnamese context. In phase 2, people with TB were invited to complete a survey containing the VTSS, a depression scale, and a quality of life scale. The data analysis included confirmatory factor analysis (CFA), exploratory factor analysis (EFA), construct validity, and floor or ceiling effects. Results: In phase 1, items were reworded from the third person to the first person. The TB/HIV co-infection items (items 7 and 11) were the least relevant for people with TB (62% and 73% relevance, respectively). In phase 2, the CFA demonstrated adequate goodness-of-fit indices (GFI = 0.88, CFI = 0.96, RMSEA = 0.058); however several of the item factor loadings were low. The EFA demonstrated good internal consistency (α = 0.85) and revealed one dominant factor. Construct validity was low. Conclusions: The VTSS demonstrated good psychometric properties in Vietnam. Depending on the purpose of the scale, the HIV co-infection items and item 10 could be considered for removal.